A Novel Approach of Threshold Setting for the Detection of Islanding in Distribution Generation-based Micro Grid - MISRA, S.; JHA, B.; MISHRA, V. M. (Advances in Electrical and Computer Engineering)
The reliable threshold setting for islanding detection is now essential due to the growing integration of distributed generators into the utility power supply. In this connection, this paper demonstrates a novel differential threshold methodology to set the detection level that is more effective than traditional absolute threshold techniques. To set the value of the detection level for operating the relay, the two instants i.e. islanding and non-islanding are taken into consideration. This novel technique is a passive method that is deployed to a test system consisting of four Distributed Generation units integrated into a radial distribution network. The proposed methodology is validated by applying five different techniques, namely Rate of Change of Active Power, Rate of Change of Reactive Power, Rate of Change of Voltage, Rate of Change of Frequency, and Rate of Change of Phase Angle Difference. The obtained numerical results are thus promising and have been compared with the numerical values of published literature. The method also has the ability to discriminate the interruptions in islanding and non-islanding events. The relay has not maloperated in non-islanding events such as short circuit whereas the proper operation of relay is demonstrated during severe grid interruptions.